Pola Komunikasi Pembimbing Magang Internal dan Eksternal dalam Mengarahkan Mahasiswa di Dinas PUTR Provinsi Sulawesi Selatan - Syam, Ayu Lestari Putri (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2023)
The purpose of this study was to determine the communication patterns of internal and external internship supervisors at the PUTR prov sulsesl office and the inhibiting and supporting factors in the direction process of internal and external internship supervisors at the PUTR prov sulsel office. The type of research used is qualitative research with data collection techniques of observation, interviews, and documentation. Furthermore, the data was analyzed using data reduction techniques, data presentation, data triangulation. The results of this study indicate that (1) there are two communication patterns used by internal internship supervisors in directing internship students, namely silkular communication patterns, secondary communication patterns. Then the communication patterns used by external internship supervisors in directing internship students are secondary communication patterns, secondary communication patterns, linear communication patterns (2) the inhibiting factors of internal and external internship supervisors in directing students at the South Sulawesi provincial PUTR office are unclear delivery of directions, stylistic pleasure, students do not understand the philosophy of internships, and the system of the public sector tends to be closed. While the supporting factors are technology and needs.